Some Aspect of Islamic Communication in First Mecca Period: A Historical Review - Istiqomah, Imroatul; Fakhirullah, Muhammad Iqbal (Proceeding International Conference on Religion, Science and Education, 2022)
The da’wah conveyed by the Prophet SAW used several methods Among them are Bil Hikmah, Mujadalah, Mauidzotul Khasanah. Prophet Muhammad SAW used several methods based on the situation what happened at that time, so that the Prophet adjusted the conditions of the people of the City Mecca at the time of preaching. The dominant method used by the Prophet Muhammad SAW at the time of his da’wah in Mecca was the Bill of Wisdom Method. This is based on when people were not familiar with Islam so that the Prophet taught good things to the people of Mecca together the purpose of his da’wah was well received. Da’wah of the Prophet Muhammad is an activity that is carried out consciously to convey Islamic messages to others so they are accept Islamic teachings and practice them well. Prophet Muhammad SAW spread Islam through preaching. The da’wah communication used by the Prophet SAW was like delivery to those closest to them so that they can easily accept the teaching delivered by the Prophet Muhammad SAW.